Media Flashcards Berbantuan Qr Code Untuk Keterampilan Menulis Bahasa Prancis Siswa Kelas XI SMA Negeri 16 Bandar Lampung - Ikhtiarti, Endang; Amalia, Riska Putri; Rini, Setia (Universitas Lampung, 2024)
The research aims to develop a learning medium in the form of Flashcards assisted by QR Codes to enhance the descriptive paragraph writing skills in French for 11th-grade students, focusing on the topic